2017
DOI: 10.1007/s13300-017-0233-z
|View full text |Cite
|
Sign up to set email alerts
|

Fasting, Diabetes, and Optimizing Health Outcomes for Ramadan Observers: A Literature Review

Abstract: IntroductionGlobally, and in Australia, diabetes has become a common chronic health condition. Diabetes is also quite prevalent in culturally and linguistically diverse pockets of the Australian population, including Muslims. There are over 90 million Muslims with diabetes worldwide. Diabetes management and medication use can be affected by religious practices such as fasting during Ramadan. During Ramadan, Muslims refrain from oral or intravenous substances from sunrise to sunset. This may lead to many potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 40 publications
0
15
0
4
Order By: Relevance
“…29 The positive effects of empowerment with the FAST tool on glycemic control were mirrored by a systematic review of Ramadan-specific education interventions, in which improvements in HbA 1c level were observed (effect size range: -1.14% to +1.70% [-12.5 to +18.6 mmol/mol]). 9 The present study also provided evidence for health care clinicians to incorporate cul- turally tailored modifications in the glucose-lowering regimen during Ramadan. 5,18 The universal uptake of modifications in glucose-lowering regimen with the use of the FAST tool maintained good glycemic control for individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…29 The positive effects of empowerment with the FAST tool on glycemic control were mirrored by a systematic review of Ramadan-specific education interventions, in which improvements in HbA 1c level were observed (effect size range: -1.14% to +1.70% [-12.5 to +18.6 mmol/mol]). 9 The present study also provided evidence for health care clinicians to incorporate cul- turally tailored modifications in the glucose-lowering regimen during Ramadan. 5,18 The universal uptake of modifications in glucose-lowering regimen with the use of the FAST tool maintained good glycemic control for individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 62%
“…8 In addition, the practice of Ramadan fasting increases the risks of complications of acute diabetes, such as hypoglycemia, hyperglycemia with or without ketoacidosis, dehydration, and thrombosis, in poorly managed patients. 5,9 Thus, fasting during Ramadan entails abrupt shifts in meal timing and physical activities, which affect circadian rhythmicity and lifestyle behaviors. 5,7,8 Although Islamic law exempts the sick from fasting, Ramadan fasting remains a deeply rooted sociocultural practice that provides spiritual enhancement and social cohesion among observant Muslims with type 2 diabetes, with up to 94.2% reported to fast for at least 15 days during Ramadan.…”
Section: Introductionmentioning
confidence: 99%
“…It is also essential for individuals with diabetes to be able to effectively manage their blood glucose and avoid severe hypoglycaemia and hyperglycaemia episodes and ultimately DKA. Previous studies have demonstrated the effectiveness of Ramadan-specific education in type 2 diabetes (Almansour, Chaar, & Saini, 2017). Optimum diabetes management can be achieved through pre-Ramadan education and dose adjustments for both type 1 and type 2 diabetes (Hassanein et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available guidelines for people with diabetes planning to fast on Ramadan are based on expert opinions. However, there is a lack of scientific evidence on the safety of fasting in people with diabetes [4,5].…”
Section: Introductionmentioning
confidence: 99%